Keterkaitan Hukum Privatisasi BUMN Terhadap Kewenangan Negara - Intan Qurratulaini; Muhajir Muhajir; Alif Saqrani; Fatir Afwa (Glossary : Jurnal Ekonomi Syariah, 2023)
Privatization of State-Owned Enterprises (BUMN) in Indonesia. Privatization is undertaken with the intention of enhancing company performance, contributing to the country's economy, and improving less efficient management. However, there are concerns regarding the loss of economic sovereignty through privatization. The Indonesian government has implemented a privatization policy based on the 1999 GBHN and the 2003 BUMN Law. Privatization has various dimensions and objectives, including reducing the state's role in the economy, increasing management efficiency, and filling the state budget deficit. The role of BUMN in development has been significant, but there have also been cases of poor management and financial losses. Privatization of BUMN is considered to overcome this problem and improve company performance. However, there are challenges in achieving professionalism and competitiveness in BUMN because employee status is like civil servants. There is also controversy regarding privatization, with some arguing that certain sectors should remain under government control in the interests of the economy. The privatization of BUMN is regulated by the BUMN Law, which emphasizes the importance of transparency, accountability, and fairness in the privatization process. However, there are concerns regarding the consistency of these regulations with the Constitution. Therefore, it is recommended that there be restrictions on the sale of shares during privatization and that the government maintain majority ownership of the shares. Apart from that, a clear definition is needed for the purpose of privatization and more detailed regulations in the BUMN Law.